2018
DOI: 10.7717/peerj.4940
|View full text |Cite
|
Sign up to set email alerts
|

Molecular attributes and apoptosis-inducing activities of a putative serine protease isolated from Tiger Milk mushroom (Lignosus rhinocerus) sclerotium against breast cancer cellsin vitro

Abstract: BackgroundThe highly valued medicinal tiger milk mushroom (also known as Lignosus rhinocerus) has the ability to cure numerous ailments. Its anticancer activities are well explored, and recently a partially purified cytotoxic protein fraction termed F5 from the mushroom’s sclerotial cold water extract consisting mainly of fungal serine proteases was found to exhibit potent selective cytotoxicity against a human breast adenocarcinoma cell line (MCF7) with IC50 value of 3.00 μg/ml. However, characterization of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Lignosus rhinocerus (LR), known as the tiger milk mushroom, is traditionally used as folk medicine in Southeast Asia and China. The medicinally beneficial part of LR is the sclerotium, an underground hardened part of the mushroom 1 that has been reported to have several medicinal properties such as neurostimulation, 2 immunomodulation, anti-inflammation, 3 anti-oxidation, anti-proliferation, 4 , 5 anti-diabetes 6 and especially antiviral activity. 7 …”
Section: Introductionmentioning
confidence: 99%
“…Lignosus rhinocerus (LR), known as the tiger milk mushroom, is traditionally used as folk medicine in Southeast Asia and China. The medicinally beneficial part of LR is the sclerotium, an underground hardened part of the mushroom 1 that has been reported to have several medicinal properties such as neurostimulation, 2 immunomodulation, anti-inflammation, 3 anti-oxidation, anti-proliferation, 4 , 5 anti-diabetes 6 and especially antiviral activity. 7 …”
Section: Introductionmentioning
confidence: 99%
“…Serine proteinase contributes to the antiviral activity of edible mushrooms [ 30 , 31 ]. Moreover, Yap et al (2018) reported a strong selective cytotoxicity of serine proteinase in the face of a human breast adenocarcinoma cell line (MCF7) and suggested that the mechanism involves the collaborative effect of both extrinsic and intrinsic cell death mechanisms, in addition to the stimulation of caspase-8 and -9 and inhibition of Bcl-2 [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…MCF7 cells were treated with HMWp at IC 50 value for 24 h, 48 h and 72 h. Total protein was extracted from the treated cells by using RIPA lysis buffer as described by Yap et al (2018) . Thirty micrograms of protein were separated on 12.5% SDS-PAGE and transferred onto polyvinylidene difluoride membrane.…”
Section: Methodsmentioning
confidence: 99%
“…The cold water extract prepared from sclerotium of L. rhinocerus has also been reported to exhibit cytotoxicity against of a panel of human adenocarcinoma and carcinoma cell lines including breast, lung, leukemic, liver, colorectal, prostate, oral squamous and nasopharyngeal cancers, and proteins and polysaccharide-protein complexes have been hypothesized as the active cytotoxic components ( Lee et al, 2012 ; Lau et al, 2013 ). A subtilisin-like serine protease fraction purified from L. rhinocerus sclerotia was also shown to exhibit cytotoxicity against MCF7 cells via induction of apoptosis ( Yap et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%